Determining the Role of Oxygen Vacancies in the Photocatalytic Performance of WO3 for Water Oxidation - Corby,S; Francàs,L; Kafizas,A; Durrant,JR (2019)
Oxygen vacancies are common to most metal oxides, whether intentionally incorporated or otherwise, and the study of these defects is of increasing interest for solar water splitting. In this work, we examine nanostructured WO3 photoanodes of varying oxygen content to determine how the concentration of bulk oxygen-vacancy states affects the photocatalytic performance for water oxidation. Using transient optical spectroscopy, we follow the charge carrier recombination kinetics in these samples, from picoseconds to seconds, and examine how differing oxygen vacancy concentrations impact upon these kinetics. We find that samples with an intermediate concentration of vacancies (~2% of oxygen atoms) afford the greatest photoinduced charge carrier densities, and the slowest recombination kinetics across all timescales studied. This increased yield of photogenerated charges correlates with improved photocurrent densities under simulated sunlight, with both greater and lesser oxygen vacancy concentrations resulting in enhanced recombination losses and poorer J-V performances. Our conclusion, that an optimal – neither too high nor too low – concentration of oxygen vacancies is required for optimum photoelectrochemical performance, is discussed in terms of the impact of these defects on charge separation and transport, as well as the implications held for other highly doped materials for photoelectrochemical water oxidation.